Tying It All Together: The Potential of Legal, Social and Market-Based Control Mechanisms to Enforce Integrated and Sustainable Decision-Making - Martin, Isabelle (Revue générale de droit, 2014)
Integrated and sustainable decision-making, which requires directors of corporations to take into account environmental, social and economic issues into their decision process, is the “keystone” of the legal principles of corporate social responsibility. A voluntary form of the principle of integrated and sustainable decision-making is part of Canadian corporate law since the enlargement of corporate directors’ duties of loyalty in the BCE decision. Although socio-legal literature has shown that voluntary principles may have a real regulatory impact, the effectiveness of a voluntary principle of integrated decision-making in furthering social and economic issues has still not been assessed. This article will argue that in order to determine the potential of integrated decision-making in ensuring greater corporate social responsibility, it is necessary to study the legal, social and market-based control mechanisms by which integrated decision-making is implemented. To what extent do these control mechanisms enforce the principle of integrated decision-making, given the unequal access of stakeholders to these control mechanisms and the competing norms of shareholder primacy and share value maximization they carry? We find that while each of the regulatory mechanisms could be used to implement the principle of integrated decision-making, no mechanism alone is sufficient to ensure that social responsibility will trump financial considerations if a choice has to be made. The analysis concludes on the regulatory courses of action that could be taken to strengthen the principle of sustainable and integrated decision-making.